A RARE CASE OF PACHYONYCHIA CONGENITA TYPE-1 FROM PAKISTAN - Shah, Nazish; Khan, Sulhera; Mirza, Reema; Talat, Humaira; Mala, Pashp (Journal of Ayub Medical College Abbottabad, 2024)
Pachyonychia congenita (PC) is a rare, genodermatosis inherited in an autosomal dominant pattern. Less than 500 cases have been reported in the literature worldwide. The disease commonly affects the nails with the typical findings of subungual hyperkeratosis and discolored nails, skin thickening of the palms and soles causing focal palmoplantar hyperkeratosis and keratoderma. In some patients, the oral mucosa may also be affected by leukokeratosis, natal teeth and hoarseness of voice. There may be the presence of keratosis pilaris, epidermal cysts and steatocystoma multiplex. We present a classical case of pachyonychia congenita type 1 that fulfils the diagnosis with the typical clinical findings of subungual hyperkeratosis, palmoplantar keratoderma and oral leukokeratosis. Our case is one of the first few cases reported from a developing country like Pakistan in the literature.